Forensic Odontology, a Boon and a Humanitarian Tool: A Literature Review - Kaleelullah, Roohi Afshan (Cureus, 2020)
Our society faces fresh challenges in every conceivable way, from an increase in the crime rate to a rise in natural disasters. In spite of the leaps in modern technology, medical breakthroughs in the identification of criminals remain a cumbersome task.  The modern-day criminal investigation typically involves many different disciplines to solve a crime. The identification of a person's body is required when it is completely mutilated, disfigured, or beyond recognition -- which might be due to any barbaric crime, accident, war, fire, or any natural disaster. Dental identification is one of the most reliable methods, as teeth and dental structures may survive adverse conditions. The techniques involved in forensic odontology include: bite mark analysis, tooth prints, rugroscopy, cheiloscopy, dental DNA analysis, radiographs, and photographs.